Activation of cytosolic RNA sensors by endogenous ligands: roles in disease pathogenesis - Straub, Sarah; Sampaio, Natalia G. (Frontiers in Immunology, 2023)
Early detection of infection is a central and critical component of our innate immune system. Mammalian cells have developed specialized receptors that detect RNA with unusual structures or of foreign origin – a hallmark of many virus infections. Activation of these receptors induces inflammatory responses and an antiviral state. However, it is increasingly appreciated that these RNA sensors can also be activated in the absence of infection, and that this ‘self-activation’ can be pathogenic and promote disease. Here, we review recent discoveries in sterile activation of the cytosolic innate immune receptors that bind RNA. We focus on new aspects of endogenous ligand recognition uncovered in these studies, and their roles in disease pathogenesis.